A logical network-based drug-screening platform for Alzheimer’s disease representing pathological features of human brain organoids - Jong-Chan Park (Nature Portfolio, 2021)
Developing effective drugs for Alzheimer’s disease (AD), the most common cause of dementia, has been difficult because of complicated pathogenesis. Here, the authors report an efficient network-based drug-screening platform developed by integrating mathematical modeling and the pathological features of human cerebral organoids.